Islamic Populism and Political Parties: PPP Electoral Failure in the Middle of the Islamic Populism Movement in the 2019 Election - Pangestu, Rexsy; Fathy, Rusydan (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. This study discusses the decline in the vote acquisition of Partai Persatuan Pembangunan (PPP) in the midst of the Islamic populism movement in the 2019 Election. As an Islamic party, this momentum should be a turning point for PPP to become a party that listens to the aspirations or interests of Muslims, as one of the task of political parties in a democratic country is as an aggregation of interests. This study uses qualitative research methods with primary data from interviews and secondary data from library studies. Based on the reading of these data, it can be seen that the failure of PPP to gain vote incentives from the Islamic populism movement in the 2019 elections is; first, the failure to create a good institutional system. This poor institutionalization is reflected in the PPP's internal conflicts. Second, there is a split in the political orientation of Indonesian Muslims in conservatism and moderatism which is clearly depicted in the 2019 election. Third, there is a change in the political orientation of the Indonesian Islamic community which places religion not as the only foothold in their political choices. People choose political parties not based on who is the most Islamic, pious, or representing the aspirations of Muslims, but based on the performance and work programs offered by the party. Keywords: PPP, Islamic Populism, 2019 Election, Party Institutionalization. Abstrak. Penelitian ini membahas perihal panurunan perolehan suara Partai Persatuan Pembangunan (PPP) di tengah gerakan populisme Islam pada Pemilu 2019. Harusnya sebagai partai Islam momentum ini adalah titik balik bagi PPP untuk bisa menjadi partai yang mendengar aspirasi atau kepentingan umat Islam, sebagaimana salah satu tugas partai politik dalam negara demokrasi yakni sebagai agregasi kepentingan. Penelitian ini menggunakan metode penelitian kualitatif dengan data primer dari hasil wawancara dan data sekunder dari hasil kajian Pustaka. Berdasarkan pembacaan terhadap data-data tersebut terlihat bahwa kegagalan PPP meraih insentif suara dari gerakan populisme Islam pada Pemilu 2019 adalah; pertama, kegagalan menciptakan sistem kelembagaan yang baik. Kelembagaan yang tidak baik ini tergambar dari konflik internal PPP. Kedua, adanya keterbelahan orientasi politik umat Islam Indonesia dalam konservatisme dan moderatisme yang tergambar kuat dalam Pemilu 2019. Ketiga, adanya perubahan orientasi politik masyarakat Islam Indonesia yang menempatkan agama bukan sebagai pijakan satu-satunya dalam pilihan politiknya. Masyarakat memilih partai politik bukan berdasarkan siapa yang paling Islam, salih, atau mewakili aspirasi umat Islam, namun berdasarkan kinerja dan program kerja yang ditawarkan partai.Kata Kunci: PPP, Populisme Islam, Pemilu 2019, Pelembagaan Partai Politik.